Second annual report of the Hospital for Natural Healing : 1936-7 - Hospital for Natural Healing (London, England) (1937)
1937 1937 1930s 13 pages who are in a position to judge where they are able to receive the benefit they require. The Ministry of Heatth is constantly informed of our activities. The following letter was sent to the Minister of Health after he had already refused on several occasions to come and see our work:— Hospital for Natural Healing, 237 Romford Road, Forest Gate, E.7. June 8th, 1937. The Rt. Hon. Sir Kingsley Wood, P.C. The Ministry of Health, Whitehall. Dear Sir Kingsley, On Thursday, September 2nd* we are celebrating our second birthday and are inviting the public to a meeting when we are going to explain our methods and ideals. As we are continually being asked certain questions relating to the working of this institution and the public, we feel that it would be advisable to answer them in public. The difficulty is that we are not in a position to give satisfactory answers to these questions and therefore I have been asked to let you have them and ask if you would be good enough to let us have your answers before September 2nd.* It would, of course, be much more satisfactory from all points of view if you could come and answer them personally or send a representative to do so, but we fear that is asking too much and shall be satisfied if you will let us have your written answers so that we may pass them on. The questions referred to are:— 1. Why does this institution, if it pays a member of the staff have to stamp that employees card although the employee has expressed the wish not to be insured and never consults a registered medical man and is therefore unable to receive medical benefit? Actually this institution is making a donation to the N.H.I. fund which is hardly justifiable when our funds are from voluntary contributions given for the sole purpose of aiding this institution. We have tried the machinery for individuals who wish to contract out of the Act but this got us nowhere. The N.H.I. Act was passed to help the people not to hinder them and restrict their freedom, therefore it is felt that there must be some means of adjusting this matter. 4 292/842/2/237